Weed Management in Pastures and Rangeland—2022: SS-AGR-08/WG006, rev. 01/2022 - Sellers, Brent A.; Devkota, Pratap (EDIS, 2022)
This publication provides practical pasture and rangeland weed management information. Written by Brent Sellers and Pratap Devkota, and published by the UF/IFAS Agronomy Department, revised January 2022.